Global Mental Health Latin America and Spanish-Speaking Populations - Escobar, Javier I (Rutgers Global Health, 2020)
Global Mental Health provides an outline of the field of mental health with a particular focus on Latin America and the Spanish-speaking world. The book details evidence-based approaches being implemented globally and presents ongoing state of the art research on major mental disorders taking place in Latin America, including work being done on understanding Alzheimer's, Bipolar Disorder, Schizophrenia, and other psychoses. While supporting the initiative for building capacity of care in low income countries, the book warns about some of the potential risks related to the abuse of psychiatry, using examples from the past, focusing on early 20th century Spain